Outcomes of Posterior-Stabilized Compared with Cruciate-Retaining Total Knee Arthroplasty - Longo, Umile Giuseppe; Ciuffreda, Mauro; Mannering, Nicholas; D'Andrea, Valerio; Locher, Joel; Salvatore, Giuseppe; Denaro, Vincenzo (The Journal of Knee Surgery, 2018)
The aim of this systematic review is to compare clinical outcome scores, rate of complications, and range of motion (ROM) of posterior-stabilized (PS) and cruciate-retaining (CR) total knee arthroplasties (TKAs) both pre- and postoperatively to establish which of the two kinds of implants have the best efficiency. A comprehensive search was performed of studies comparing CR and PS TKAs on PubMed, OVID/Medline, Cochrane, CINAHL, Google scholar, and Embase databases. Finally, 37 studies were selected with a total of 5,407 knees in 4,445 patients. For the PS knees, the Knee Society Functional Score (KSFS) improved from 44.6 to 77.6 (p = 0.04), extension decreased from 6.6 to 1.8 degrees (p-value), and flexion increased from 115.2 to 119.4 degrees (p < 0.00001), compared with the CR knees. No significant difference in the Knee Society objective score (KSOS) (p = 0.82) or complication rates (p = 0.29) was found. The overall complication rate was 3.9%, 213 in 5,407 knees. Surgeons must be careful in interpreting these results, as an improved ROM for the PS group may not correlate to better patient outcomes. This meta-analysis has demonstrated that PS TKA has a statistically significant greater postoperative improvement of KSFS (p = 0.04), flexion (p < 0.00001), and extension (p = 0.02), compared with the CR group. These findings seem to lead the surgeons to prefer the PS design for TKAs especially to achieve a higher postoperative ROM in patients with high functional demands. On the contrary, the CR and PS TKAs have similar results in terms of complications and most of clinical outcomes analyzed in the included studies. Therefore, the long-term follow-up of high-quality randomized controlled trials is needed to clarify which of the two types of prosthesis provide the better clinical outcome and the lower rate of complications for osteoarthritis patients in particular cohorts. This is a systematic review (level II).
Keywords: knee; arthroplasty; cruciate-retaining; posterior-stabilized